Enteral tube feeding practices and associated factors among nurses working in South Wollo Zone Specialized and General Hospitals, Wollo, Ethiopia, 2022 - Ahmed, Ali; Anteneh, Samuel; Hussien, Adem; Seid, Anwar; Semanew, Yaregal (Frontiers in Nutrition, 2024)
In critically ill patients, enteral tube feeding is recommended as a route for nutrient delivery. Nurses' practice of enteral tube feeding influences patient treatment outcomes. Therefore, this study aimed to identify enteral tube feeding practice and associated factors among nurses working in South Wollo Zone Specialized and General Hospitals, Wollo, Ethiopia 2022.: A Hospital-based cross-sectional study design was conducted on 420 nurses from August1-September1 2022. Simple random sampling methods were used to select study participants. Data was collected by self-administering questionnaires and an observational checklist. The data were entered into Epi Data version 4.6 and analyzed with SPSS version 26.Variables having a p-value less than 0.05 with a 95% confidence interval and adjusted odd ratio were stated significantly associated with enteral tube feeding practice.Result: A total of 400 nurses participated in the study with a 95.2% response rate. The overall good practice of nurses on enteral tube feeding was 114 (28.5 %) with (95% CI: 23.8-33). Enteral tube feeding practice was significantly associated with a lack of adequate resources (AOR=0.359, 95% CI: 0.192 -0.673, nurses unfamiliar with current guidelines (AOR= 0.346, 95% CI: 0.203-0.586), lack of awareness (AOR=0.511, 95%CI: 0.306, 0.673) and thermal effect of food (AOR=0.56, 95% CI 0.348-0.889).EnteralThe overall good enteral tube feeding practice of nurses was 114(28.5%); Lack of awareness, inadequate resources in the institution, and unfamiliarity with the current guidelines of enteral feeding were the identified significant determinates of enteral tube feeding practice. For better enteral feeding practice, availing sufficient resources, and guidelines and providing training are some of the authors' recommendations.